The Use of a Digital Groundwater Model in the Environmental Impact Assessments - I, Yusoff; Abd Ghani M. A, Wan (Malaysian Journal of Science, 2005)
Aquaculture activities have numerous environmetal impacts on groundwater resources and water quality. Groundwater modelling technique was used to study the impacts of groundwater abstraction for aquaculture in Nenasi, Pekan Pahang. The objectives of the study were to study the hydrogeological conditions of the area, to highlight any possible impacts on groundwater resources caused by over abstraction and to determine the permissible groundwater abstraction rate. The modelling results suggested that over abstraction would lower down groundwater level, dry up the shallow aquifer and induce the salt water intrusion. Other than that, the model suggested that the maximum abstraction rate is not more than 150,000 cubic metres per day.